Studies of the Adsorption Behaviours of Reactive Brilliant Blue K-NR on Silver by Surface-Enhanced Raman Scattering - Zhimei, Li; Yizhen, Wang; Chongbin, Wen (Asian Journal of Chemistry, 2010)
The adsorption behaviours of reactive brilliant blue K-NR adsorbed on silver mirror were studied using the surface-enhanced Raman scattering. The adsorptive mechanisms of reactive brilliant blue K-NR were discussed. The results indicated that silver could greatly enhance Raman scattering responses. The surface-enhance Raman scattering intensity of reactive brilliant blue K-NR varied its and blue K-NR concentration was adsorbed on silver mirror through electrostatic force and van der Waals force.